2006
DOI: 10.1002/anie.200504379
|View full text |Cite
|
Sign up to set email alerts
|

A Direct CO Polymer Electrolyte Membrane Fuel Cell

Abstract: A good source of energy: The reformation of hydrocarbons generates CO as well as H2. Despite its high reducing activity, CO is not suitable as a fuel in polymer electrolyte membrane fuel cells (PEMFCs) because it is a strong poison for the Pt catalyst used as the anode. A new fuel cell has now been developed with a rhodium octaethylporphyrin ([Rh(oep)]) anode catalyst that uses neat CO as a fuel, and delivers high performance (see graph).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 25 publications
(44 reference statements)
0
32
0
Order By: Relevance
“…Among them, radiation-induced graft polymerization of pre-existing polymer materials is well known for its merits and potential in modifying the surface properties of pre-existing polymer materials without changing their inherent properties [2]. In sharp contrast to most focuses on surface modification, little attention has been paid to uniformly bulk graft modification of pre-existing polymer materials, which has great potential application in preparing impact-resistant plastics, thermoplastic elastomers, and polymer electrolyte membranes suitable for uses in fuel cells, batteries and sensors [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, radiation-induced graft polymerization of pre-existing polymer materials is well known for its merits and potential in modifying the surface properties of pre-existing polymer materials without changing their inherent properties [2]. In sharp contrast to most focuses on surface modification, little attention has been paid to uniformly bulk graft modification of pre-existing polymer materials, which has great potential application in preparing impact-resistant plastics, thermoplastic elastomers, and polymer electrolyte membranes suitable for uses in fuel cells, batteries and sensors [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Rh porphyrins can oxidize CO at low overpotentials [8][9][10][11]. The best catalyst we identified in our studies can catalyze CO oxidation even below 0.1 V vs. RHE at 25°C [10].…”
Section: Introductionmentioning
confidence: 92%
“…Against this background, we studied Rh porphyrin-based CO oxidation catalysts to counteract the problem of CO [8][9][10]. Rh porphyrins can oxidize CO at low overpotentials [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it is demonstrated that carbon-supported Rh porphyrin catalysts have strong activity for the electrooxidation of several small molecules (CO, glucose, and oxalic acid) [33][34][35][36]. The reduction of hydrolysis on the anode catalyst is important for the improvement of DBFCs.…”
Section: Borohydridementioning
confidence: 99%